Patients' Attitudes to Medical Students in General Practice - Wright, H. J. (1974)
259 consecutive adult patients were interviewed regarding their attitudes to the presence of medical students at consultation, at examination, and at home visits. Few patients declared reluctance to discussing physical illness and smoking or drinking problems in the student's presence, but many had appreciable inhibitions about discussing almost every other common component of consultation. Over half of the younger women interviewed would prefer students not to be present at physical or pelvic examination. Neither age nor social class showed significant association with declared preference, but previous contact with students did not decrease inhibitions among patients. Only 15% of respondents said that they would be more upset by the presence of two students rather than one.